Analisis Faktor Yang Memengaruhi Pemilihan Jenis Kontrasepsi Pada Pasaangan Usia Subur di RSUD Batara Siang - Nurdalifah Nurdalifah (Universitas Muhamadiyah Manado, 2020)
Indonesia is a developing country with a high population increase. The increasing population situation makes it difficult to improve and equalize people's welfare. The higher the population growth, the greater the efforts made to maintain people's welfare. One strategy to reduce the birth rate is through the use of contraception. However, there are several factors that influence the choice of contraception, including level of knowledge, age, birth spacing and parity and postpartum counseling. So this research aims to explain the analysis of factors that influence the choice of type of contraception in couples of childbearing age at Batara Siang Regional Hospital. Research Design: The type of research is quantitative descriptive correlation with a cross sectional design. The population in this study was all family planning acceptors at Batara Siang Regional Hospital in April 2020. The research sample was 47 couples of childbearing age at Batara Siang Regional Hospital using an accidental sampling technique. The results of the research show that the p value obtained from the Wald test for the age variable is 0.039, which means there is a relationship between age in choosing a contraceptive method. This relationship is statistically significant (OR= 11.139; p = 0.039), the education variable shows that the p value obtained from the Wald test for the education variable is 0.014, which means there is a relationship between education and the choice of long-term contraceptive methods. Conclusion: There is a significant influence between age and education and the choice of type of contraception in couples of childbearing age at Batara Siang Regional Hospital.